IPAC Nieuws. - Interprovinciaal Aidscoördinaat (IPAC) (Antwerpen : IPAC, 1994)
Fonds Suzan Daniel (FSD)
Periodiciteit: driemaandelijks
Redactie: Marnixplaats 16-17, 2000 Antwerpen
Nederlands
Periodiek